PROSES IMPLEMENTASI BANTUAN OPERASIONAL SEKOLAH (BOS) DI SMK NEGERI 7 KOTA SEMARANG - Rifka Resi Pawestri; Warsito .; Lusia Astrika (Journal of Politic and Government Studies, 2015)
School Operational Assistance Fund is a central government assistance to all schools Elementary and Junior High School, including the Open High School, High School, Vocational High School and The Independent Learning Activities held by the community, both public and private in all provinces in Indonesia. With the School Operational Assistance program funding, schools are required ability to be able to plan, implement and evaluate and be accountable for the management of the educational costs transparent to the public and the government.The study, titled Process Implementation of School Operational Assistance (BOS) at SMK Negeri 7 Semaarang City aims to determine the process of implementation of the BOS program at SMK Negeri 7 Semarang. In addition, to know the various problems that arise in implementing the Operational School in SMK Negeri 7 Semarang. This study uses a mixed method research with data collection through interviews and questionnaires.Based on the results of the study showed that the level of effectiveness of the implementation process of the School Operational Assistance (BOS) at SMK Negeri 7 of Semarang is influenced by several factors, factors Human Resources (HR), communication, attitudes implementing and coordinating factor. The problems that must be faced by schools is their failure to provide socialization of BOS to parents, the failure in the manufacture of LPJ, as well as ignorance of the teachers of the operational guidelines BOS policy guidelines. These constraints can occur because BOS Program is a new program so that schools need time to adapt and get used to all regulatory guidelines elaborate guidelines.